2012
DOI: 10.1182/blood-2011-10-384826
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl leukotriene overproduction in aspirin-exacerbated respiratory disease is driven by platelet-adherent leukocytes

Abstract: Cysteinyl leukotriene (cysLT) overproduction is a hallmark of aspirin-exacerbated respiratory disease (AERD), but its mechanism is poorly understood. Because adherent platelets can convert the leukocytederived precursor leukotriene (LT)A 4 to LTC 4 , the parent cysLT, through the terminal enzyme LTC 4 synthase, we investigated the contribution of platelet-dependent transcellular cysLT production in AERD. Nasal polyps from subjects with AERD contained many extravascular platelets that colocalized with leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
211
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(222 citation statements)
references
References 51 publications
10
211
0
1
Order By: Relevance
“…Platelets lack 5-LO, but possess LTC 4 S and convert unmetabolized LTA 4 to LTC 4 when they adhere to the granulocyte surface via P-selectin (54). We previously demonstrated that platelet-adherent eosinophils and neutrophils are more frequent in the peripheral blood and sinonasal tissues from patients with AERD than in samples from aspirin-tolerant controls (9). Adherent platelets were the dominant source of LTC 4 S activity in granulocytes from subjects with AERD and they correlate with urinary LTE 4 levels (9).…”
Section: Deletion Of Hematopoietic Ep 2 Receptors Partially Reproducementioning
confidence: 99%
See 2 more Smart Citations
“…Platelets lack 5-LO, but possess LTC 4 S and convert unmetabolized LTA 4 to LTC 4 when they adhere to the granulocyte surface via P-selectin (54). We previously demonstrated that platelet-adherent eosinophils and neutrophils are more frequent in the peripheral blood and sinonasal tissues from patients with AERD than in samples from aspirin-tolerant controls (9). Adherent platelets were the dominant source of LTC 4 S activity in granulocytes from subjects with AERD and they correlate with urinary LTE 4 levels (9).…”
Section: Deletion Of Hematopoietic Ep 2 Receptors Partially Reproducementioning
confidence: 99%
“…These lesions limit basal EP receptor signaling that normally prevents the severe persistent respiratory mucosal eosinophilia. Impaired EP receptor input compromises control of TP receptor signaling by PKA (28), increasing the adherence of platelets to granulocytes, inducing endothelial ICAM-1 (28), activating 5-LO, and enabling platelet-adherent leukocytes to mediate LT generation (9). The residual local PGE 2 derives principally from COX-1, which may explain why only COX-1 active drugs provoke clinical reactions (6) and why COX-2-selective drugs are well tolerated by these patients (20).…”
Section: Deletion Of Hematopoietic Ep 2 Receptors Partially Reproducementioning
confidence: 99%
See 1 more Smart Citation
“…cysteinyl leukotrienes | mast cells | mucosal immunology | lung | epithelial cell C ysteinyl leukotrienes (cysLTs), leukotriene C 4 (LTC 4 ), LTD 4 , and LTE 4 are lipid mediators detected during asthma exacerbations triggered by allergen (1), aspirin (2,3), and respiratory viruses (4). The cysLTs elicit vascular permeability, inflammation, and bronchoconstriction through three G-protein-coupled receptors.…”
mentioning
confidence: 99%
“…Following is the series of causes of thrombocytosis, blood clotting in legs or arms, infection, diseases like anemia cancer etc [32][33][34] .…”
Section: Figurementioning
confidence: 99%